Lateral bone simplified antrostomy. A case report - Vilcapoma Guerra, Henry (2011)
This clinical report presents a simplified surgical procedure for accessing the maxillary sinus antrum via lateral approach, which reduces the potential for sinus membrane perforation and subsequent complications when graft materials and dental implants are placed into the sinus. Due to visual limitations,perforations and associated complications can jeopardize the success rate of the graft and the implants. While there is a lack of clinical data, clinical observations suggest that the procedure, described by the authors as lateral bone planing antrostomy, can reduce the possibility of perforation of the maxillary sinus membrane during the lateral approach to the grafting of the maxillary sinus floor. The technique involves the use of specially designed rotary instruments that plane away the bone in thinner layers, with less chance of excess bone removal and membrane perforation. The aim of the publication is to show the clinical sequence of the surgical procedure. We conclude that the simplified lateral bone antrostomy is simple to perform and reduces the appearance of complications.